narrative functions in Renaissance paintings - Hasan Talib Jenzy (Basrah Arts Journal, 2022)
The research dealt with (narrative functions in Renaissance paintings) and it contained four chapters. The first chapter included the methodological framework for the research, which was represented by the research problem and its goal (revealing the functions and techniques of narration in Renaissance Paintings). The limits of the research were limited to studying the functions of narration in paintings. The Renaissance period (1425-1563), which the researcher chose from books and the Internet and was analyzed according to the descriptive method. As for the second chapter, the theoretical framework and previous studies, which included two topics, the first topic: Narrative styles, techniques and functions. As for the second topic, it dealt with: visual narration, applications in Renaissance paintings. The third chapter included the research procedures that included the research community, its sample, its methodology, and the analysis of the sample of (5) works of art. While the fourth chapter includes the results of the research and conclusions, among the findings of the researcher the following: ▪ The functions of narration depend on the interrelationships towards the current context between the diagnostic forms that serve to convey the meaning and idea of the narration, which depends on the grouping and the linking relationships between the formal visual units and the organizations taking place and not on the structure of the narration. ▪ There are main functions of narration that work to build a visual narration mechanism, which are : - The communicative function, the communicative function, the ideological function, the expressive function, and the reference function, and there are techniques affiliated with these functions can establish and build visual narratives in drawing, which are the retrieval technique and the time and space technique .